Solar Cells: High Efficiency Cu2ZnSn(S, Se)4 Solar Cells by Applying a Double In2S3/CdS Emitter (Adv. Mater. 44/2014). (November 2014) - Kim, Jeehwan; Hiroi, Homare; Todorov, Teodor K.; Gunawan, Oki; Kuwahara, Masaru; Gokmen, Tayfun; Nair, Dhruv; Hopstaken, Marinus; Shin, Byungha; Lee, Yun Seog; Wang, Wei; Sugimoto, Hiroki; et al.
<x xml:space="preserve">Abstract</x> On page 7427, J. Kim, H. Hiroi, T. K. Todorov, D. B. Mitzi, and co‐workers report high‐efficiency Cu2ZnSn(S, Se)4 solar cells by applying In2S3/CdS double emitters. This new structure offers a high doping concentration within the Cu2ZnSn(S, Se)4 solar cells, resulting in substantial enhancement in the open‐circuit voltage. The 12.4% device is obtained with a record open‐circuit voltage deficit of 593 mV. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>